Teaching intercultural competence across the age range from theory to practice - Wagner, Manuela; Perugini, Dorie Conlon; Byram, Michael (Languages For Intercultural Communication And Education, 2018)
Focusing on the teaching and learning of intercultural communicative competence in foreign language classrooms in the USA, this ground-breaking book is the first to describe in detail how teachers, supported by university educators and education advisers, might plan and implement innovative ideas based on sound theoretical foundations.--Publisher description.